2017
DOI: 10.3847/1538-3881/aa974d
|View full text |Cite
|
Sign up to set email alerts
|

Tidal Synchronization and Differential Rotation of Kepler Eclipsing Binaries

Abstract: Few observational constraints exist for the tidal synchronization rate of late-type stars, despite its fundamental role in binary evolution. We visually inspected the light curves of 2278 eclipsing binaries (EBs) from the Kepler Eclipsing Binary Catalog to identify those with starspot modulations, as well as other types of out-of-eclipse variability. We report rotation periods for 816 EBs with starspot modulations, and find that 79% of EBs with orbital periods of less than 10 days are synchronized. However, a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
125
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(149 citation statements)
references
References 65 publications
11
125
5
Order By: Relevance
“…Our results are directly relevant for interpreting observational evidence for synchronization and circularization of solar-type and low-mass close binaries (e.g. Meibom & Mathieu 2005;Meibom et al 2006;Van Eylen et al 2016;Lurie et al 2017;Triaud et al 2017). We can estimate the convective turnover timescale τ cv = 2π/ω cv (e.g.…”
Section: Astrophysical Implicationsmentioning
confidence: 76%
See 3 more Smart Citations
“…Our results are directly relevant for interpreting observational evidence for synchronization and circularization of solar-type and low-mass close binaries (e.g. Meibom & Mathieu 2005;Meibom et al 2006;Van Eylen et al 2016;Lurie et al 2017;Triaud et al 2017). We can estimate the convective turnover timescale τ cv = 2π/ω cv (e.g.…”
Section: Astrophysical Implicationsmentioning
confidence: 76%
“…The range of validity of the various turbulent viscosity prescriptions is shown in Figure 4, for binaries given in Lurie et al (2017). Both scalings are shown to be relevant for this sample.…”
Section: Astrophysical Implicationsmentioning
confidence: 91%
See 2 more Smart Citations
“…The strength of the tidal force decreases as F r 1 T 3 µ , meaning an interaction with a third companion would have to occur at very close orbital separations in order to exert a sufficient tidal spin-up on the affected star. Lurie et al (2017) recently found in a sample of unresolved Kepler eclipsing binaries that tidal forces affected stellar rotation for systems with orbital periods shorter than 30 days, and typically led to orbit-spin synchronization for orbital periods shorter than 10 days. The faster rotators in the outlier pairs from our sample predominantly display P 10 rot < days.…”
Section: Hierarchical Triples and The Effects Of Tidesmentioning
confidence: 99%